ISLAM I ZAPAD U NOVOM SVJETSKOM PORETKU - Ikbal, Muzafer; Fatić, Almir (Novi Muallim, 2007)
Zafar Ishaq & John L. Esposito (ed.), Muslims and the West Encaunter Dialogue, Islamic Research Insitute & Center for Muslim-Christian Understanding, Islamabad-Washington, 2001., pp. 231-273 Prijevod s engleskog: Almir Fatić